Обгрунтування бікомпонентної кісткової пластики у комплексному лікуванні хворих на хронічний травматичний остеомієліт довгих кісток (клініко-експериментальне дослідження) - Чверкалюк О.К.; Chverkalyuk А.К. (My University, 1996)
There are 19 scientific articles under defence 4 invention certificates, that give experimental foundation the results of the performed bone plastic operations on 89 patients with chronic traumatic osteomyelitis of long bones. Biochemical immunomorphologic and histomorphologic researches show the expediency of filling up osteomyelitic cavities with annealed allo and xenogenic cancellous tissue at a clinic. Annealed xenogenic cancellous tissue is found to be biocompatible and plastic and to have low immunogenic properties; coupled with demineralized allogenic bone matrix it brings better results then monocomponent bone plastics. Metodology of bone plastic operation for replacement osteomyelitic cavities developed by the author is used in hospitals of Donetsk, Kirovograd, Dniepropetrovsk, Krivoy Rog, Lutsk.
Substantiation for biocomponent bone plastics in complex treatment of patients with chronic traumatic osteomyelitis of long bones
Keywords: traumatic osteomyelitis; fistulonecroequesrektomy; osteomyelitic cavity; long bones annealed allo - and xenogenic cancellous tissue; biocomponent bone plastics